Tax Transformation of SMEs in Bojongsoang Village: The Impact of Socialization of Government Regulation No. 55 of 2022 and Coretax Application Socialization - Dewi, Maya Safira; Fajriati, Novy; Hapsari, Dini Wahjoe; Soma, A. Mukti (Edumedia Solution, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, including in West Java. However, many MSME actors still face challenges in understanding their tax obligations. This article analyzes the impact of the socialization of tax regulation changes, specifically the transition from Government Regulation No. 23 of 2018 to Government Regulation No. 55 of 2022, as well as the implementation of the Coretax application for digital tax reporting in Bojongsoang Village, Bojongsoang District, Bandung Regency. The socialization program was conducted on October 23, 2025, involving 50 local MSME actors. The results of the socialization showed an improvement in understanding the 0.5% final income tax rate for MSMEs with revenue below IDR 4.8 billion, as well as the procedure for digital tax reporting. Although some participants expressed concerns regarding the use of Coretax, the workshop successfully provided practical understanding of how to use the application. Through this activity, it is expected that MSME actors in Bojongsoang Village will be able to manage their tax obligations more efficiently and reduce difficulties in tax administration. This community service program has the potential to enhance MSME tax compliance and support the sustainability of the MSME sector in the region.